ANALISIS EFEKTIVITAS PEMBELAJARAN DARING DAN LURING PADA ERA ENDEMIK COVID-19 - Defi Yusti Faidah; Nathanael Mareo Liatna; Anugrah Aidil Fitria; Refaldo Richkolas Philadelphia (LPPM Universitas Bina Bangsa, 2023)
The COVID-19 pandemic has brought significant changes, particularly in the education sector. Since the onset of the pandemic, closure policies and social restrictions have forced many educational institutions to find alternative solutions to keep learning going. During the COVID-19 pandemic period, the learning method used is online media. This refers to the practice of distance learning implemented to maintain social distance and reduce the spread of the virus. Online and offline learning have their own advantages and disadvantages. The purpose of this study is to determine the difference in effectiveness between online and offline learning using nonparametric statistical methods. The result of Mann-Whitney test can be concluded that there is a difference in effectiveness between online and offline learning. Chi-Square test shows that there is a relationship between learning process and understanding lecture material, interacting with lecturers and learning motivation. However, a relationship does not exist between the learning process and students' time management